The path towards buildings energy efficiency in South American countries - Silvero, F (2019)
Nowadays, energy efficiency (EE) is presented as a reliable strategy towards sustainable development, but its application has not been developed equitably worldwide, since most EE policies have been implemented in industrialised nations, and developing countries are still in the process of improving their EE levels. This paper provides a contextual framework to analyse the EE situation in countries of Latin American Southern Cone, such as Argentina, Brazil, Chile and Uruguay, with the objective of describing the policies and projects implemented, highlighting the results achieved and outlining the path followed towards EE. A focus was placed on the building sector, where thermal performance standards and the programs to achieve EE in this sector were briefly described. Furthermore, a comparison between these standards was developed, to identify the country with the most demanding standard. As a result, it was found that all the countries are implementing several EE programs and recognising the importance of this issue within their policies. Through this paper, energy policy implications of the region can be identified, which can be useful for energy policymakers of other countries, who are beginning to consider EE policies and can take as an example the path followed by the countries analysed.